Eugene Meyer papers - Meyer, Eugene, 1875-1959.
Correspondence, memoranda, minutes, diaries, oral history interviews, speeches, writings, congressional testimony, press statements, family papers, biographical material, financial records, printed matter, scrapbooks, photographs, and other papers relating to Meyer's career as a financier, public official, and publisher of the Washington Post. Focuses on American economic and financial history including agricultural and political economy, regulation of currencies, corporate finance, foreign trade, international monetary affairs, and war reparations. Materials pertaining to the Washington Post relate chiefly to the business aspects of advertising, circulation, public relations, and syndication. Subjects also include business and financial interests ranging from the automobile, airplane, and metals industries to mining, ranching, and real estate. Documents Meyer's personal and family life; his connections to the artistic community; interest in psychology, psychiatry, and mental health; philanthropic work during World War II; and travels in Europe. Includes Clover Croft School files relating to refugee children and materials concerning German Jewish refugees and the Zadoc-Kahn and Weill families.
Individuals represented include Alfred Friendly, Philip L. Graham, Sidney Hyman, and James Russell Wiggins. Corporate bodies represented include Alaska Juneau Gold Mining Company, Allied Chemical & Dye Corporation, American Institute of Public Opinion, American Radiator and Standard Sanitary Corporation, Anaconda Copper Co., Boston Consolidated Mining Company, Gallup Organization, Granby Consolidated Mining, Smelting and Power Company, Ltd., Maxwell Motors, U.S. Federal Farm Loan Board, U.S. Federal Reserve Board, War Finance Corporation, and the Washington Criminal Justice Association.
Correspondents include Bernard M. Baruch, Fred H. Bixby, Samuel G. Blythe, Gutzon Borglum, Brendan Bracken, Robert H. Brand, Louis Dembitz Brandeis, Alfred A. Cook, George R. Cooksey, Calvin Coolidge, William O. Douglas, Abba Eban, Dwight D. Eisenhower, Felix Frankfurter, Charles Freer, Alfred Friendly, Philip L. Graham, Floyd R. Harrison, Helen Hayes, James W. Hoban, Herbert Hoover, J. Edgar Hoover, Sidney Hyman, Thomas Mann, Herbert G. Moulton, Edward Rickenbacker, Nelson Rockefeller, Carl Sandburg, Edward Steichen, Earl Warren, James Russell Wiggins, Woodrow Wilson, and the Meyer (Myers) family.
Special tribute available only on microfilm
Microfilm of special tribute in private hands.
Private
Library of Congress Prints and Photographs Division.
Investment banker, financier, public official, and newspaperman.
Collection material in English.
Keywords: Baruch, Bernard M. -- 1870-1965 -- Correspondence; Bixby, Fred H. -- Correspondence; Blythe, Samuel G. -- 1868-1947 -- Correspondence; Friendly, Alfred; Friendly, Alfred -- Correspondence; Graham, Philip L., -- 1915-1963.; Hyman, Sidney; Wiggins, James Russell, -- 1903-2000.; Wiggins, James Russell, -- 1903-2000 -- Correspondence; Kahn family; Meyer family; Myers family; Weil family; Weill family; Zadoc family; United States. -- Federal Farm Loan Board; United States. -- Federal Reserve Board; Alaska Juneau Gold Mining Company; Allied Chemical & Dye Corporation; American Institute of Public Opinion; American Radiator and Standard Sanitary Corporation; Anaconda Copper Co; Boston Consolidated Mining Company; Clover Croft School; Gallup Organization; Granby Consolidated Mining, Smelting and Power Company, Ltd; Maxwell Motors; War Finance Corporation (U.S.); Washington Criminal Justice Association; Washington Post Company; Advertising; Agriculture -- United States; Aircraft industry; American newspapers -- Washington (D.C.); Arts; Automobile industry and trade; Business; Charities; Commerce; Commercial policy; Corporations -- Finance; Economic history; Economic policy; Economics; Finance; International economic relations; International economic relations; International finance; International trade; Journalism; Mental health; Metal trade; Mineral industries; Monetary policy; Newspaper publishing; Psychiatry; Psychology; Public opinion polls; Public relations; Ranching